NK cell and ILC heterogeneity in colorectal cancer. New perspectives from high dimensional data. (August 2021) - Pietropaolo, Giuseppe; Scarno, Gianluca; Stabile, Helena; Grimaldi, Alessio; Gismondi, Angela; Santoni, Angela; Sciumè, Giuseppe
Abstract: Innate lymphoid cells (ILCs) and tissue-resident natural killer (NK) cells ensure immunity at environmental interfaces and help maintain barrier integrity of the intestinal tract. This wide range of innate lymphocytes is able to provide fast and potent inflammatory responses that, when deregulated, have been associated with pathogenesis of inflammatory bowel disease (IBD) and colorectal cancer (CRC). While the presence of tumor-infiltrating NK cells is generally associated with a favorable outcome in CRC patients, emerging evidence reveals distinct roles for ILCs in regulating CRC pathogenesis and progression. Advances in next generation sequencing technology, and in particular of single-cell RNA-seq approaches, along with multidimensional flow cytometry analysis, have helped to deconvolute the complexity and heterogeneity of the ILC system both in homeostatic and pathological contexts. In this review, we discuss the protective and detrimental roles of NK cells and ILCs in the pathogenesis of CRC, focusing on the phenotypic and transcriptional modifications these cells undergo during CRC development and progression.